Computer simulation of laser destruction of synovial cysts and perianal condylomas laser vaporization - D. V. Kudrytski; S. V. Shakhrai; Yu. M. Gain (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The study determined the optimal parameters of laser radiation for the destruction of the synovial cysts and vaporization of perianal warts. The study was divided into three phases: computer modeling, experiment, and clinical research. The data obtained at each stage complement each other.